2016
DOI: 10.1080/09674845.2016.1220710
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 predicts poor prognosis in patients with osteosarcoma

Abstract: Upregulation of miR-21 was associated with poor clinicopathological characteristics. It is used as a marker of poor prognosis in patients with osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…There were 4 studies assessing miR-21 as a predictor of survival in osteosarcoma using multivariate analysis, among which 3 used tumor tissues ( n = 153) [ 5 , 54 , 61 ] and 1 used serum samples ( n = 65) [ 53 ] (Table 3 ). Once pooled, studies with different baselines showed obvious statistical heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 studies assessing miR-21 as a predictor of survival in osteosarcoma using multivariate analysis, among which 3 used tumor tissues ( n = 153) [ 5 , 54 , 61 ] and 1 used serum samples ( n = 65) [ 53 ] (Table 3 ). Once pooled, studies with different baselines showed obvious statistical heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrantly expressed miRs are implicated in the regulation of OS onset and development (23)(24)(25). Therefore, key miRs in OS must be identified to develop promising and effective therapeutic targets for patients with OS.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR21 (Fig. 2) emerges consistently as a significant marker for poor prognosis, when its expression levels in the plasma of patients with OS and cancer cells are compared with those found in controls (62)(63)(64). miR-199a, which has been shown to be dysregulated in several types of tumor, has been found to be underexpressed in osteosarcoma cells and patient samples.…”
Section: Role Of Mirnas In the Pathological Osteogenic Commitment Of mentioning
confidence: 95%